Students` perceptions about the impact of COVID-19 on learning process. A sociological approach - Apostol, Alexandru-Cosmin (Technium Social Sciences Journal, 2020)
The last six months have been marked by the worldwide spread of the new coronavirus (COVID-19) which has triggered a global pandemic crisis. Thus, among the most affected fields of activity is education, educational institutions being forced to transfer all the curricular activities in the online environment, by using various digital tools and also Social Media. Due the rapidly spreading of the novel coronavirus, since the beginning of this year, thousands of higher education institutions around the world have been gradually constrained by local gouvernments and public authorities to replace traditional in-person educational activities with distance education, mediated by the digital environment. In turn, the Romanian educational system, as in the case of other countries, has been forced to respond promptly to the arising pandemic crisis challenges. Over the past decades, several researchers from various scientific fields have shown a growing interest in studying the ways in which technology (Marchello and Kelly, 1989), information and communication technology – ICT (Campbell, 2006; Aczel and Hardy, 2007; Saadik, 2008) or digital tools (Säljö, 2010) can be successfully integrated into curricular activities. Nowadays, all these contributions acquire a special significance, once the educational system has had to adapt, willingly or unwillingly, to the current context. In this context, the purpose of this paper is to present several results of an exploratory quantitative sociological research conducted between 26th of March - 20th of April 2020, at the Faculty of Philosophy and Social-Political Sciences, Alexandru Ioan Cuza University of Iasi, on a sample of 643 students. The main purpose of this research was to highlight the impact of the pandemic crisis on the learning process among students. Among the main research objectives were: (a) to identify students perceptions about the closure of face-to-face university courses and seminars; (b) to measure the proportion of students who were considering, at the time of the study, that the Romanian educational system is ready to switch traditional learning activities with online courses and seminars; (c) to analyze the main concerns among students toward the effects of pandemic crisis on their future educational path and educational outcomes.